2015
DOI: 10.1186/s12885-015-1555-8
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of SUMO1/Sentrin specific peptidase 1 (SENP1) in prostate cancer is limited to ERG-fusion positive tumors lacking PTEN deletion

Abstract: BackgroundPosttranscriptional protein modification by SUMOylation plays an important role in tumor development and progression. In the current study we analyzed prevalence and prognostic impact of the de-SUMOylation enzyme SENP1 in prostate cancer.MethodsSENP1 expression was analyzed by immunohistochemistry on a tissue microarray containing more than 12,400 prostate cancer specimens. Results were compared to tumor phenotype, ERG status, genomic deletions of 3p, 5q, 6q and PTEN, and biochemical recurrence.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 65 publications
2
16
0
Order By: Relevance
“…PTEN deletions are linked to poor prognosis in PCa . Many prognostic features fail to further stratify patient outcome in molecular subgroups that are already defined by PTEN deletion . The significant link between low‐level survivin staining and tumor proliferation would be consistent with a role of survivin expression in the control of cellular proliferation as suggested by several authors .…”
Section: Discussionsupporting
confidence: 62%
“…PTEN deletions are linked to poor prognosis in PCa . Many prognostic features fail to further stratify patient outcome in molecular subgroups that are already defined by PTEN deletion . The significant link between low‐level survivin staining and tumor proliferation would be consistent with a role of survivin expression in the control of cellular proliferation as suggested by several authors .…”
Section: Discussionsupporting
confidence: 62%
“…Higher SENP1 expression has been hypothesized to be associated with higher androgen activity in Andean highlanders with EE [34]. Higher expression of SENP1 has been documented to induce HIF-1α and reduce apoptosis, thus promoting the development or progression of prostate [35] and other cancer [36,37] cells. Recently, absence of SENP1 has been reported to produce inflammatory cytokines, leading to type 1 diabetes in a murine model [38], and reduced expression led to impaired glucosedependent insulin exocytosis in an in vitro human islet model [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, many studies reported that SENP1 was overexpressed in human prostate cancer (CaP) cells (9), as well as lung cancer tissues (10) and most of colon cancer tissues (11). The expression of SENP1 was reported to have strong prognostic impact on a molecularly defined subset of CaPs (12). Another study revealed that SENP1 might be a prognostic marker and a therapeutic target for metastasis in CaP patients, for its roles in regulating MMP2 and MMP9 through the HIF-1α signaling pathway (13).…”
Section: Introductionmentioning
confidence: 99%